Laparoscopy is the Gold Standard in Ovarian Pathologies in Childhood: Clinical Evaluation and Literature Review - Gülnur Göllü; Ufuk Ateş; Nil Yaşam Taştekin; Ergun Ergün; Meltem Bingöl Koloğlu; Aydın Yağmurlu; Tanju Aktuğ; Hüseyin Dindar; Ahmet Murat Çakmak (Medical Network, 2016)
OBJECTIVE:Ovarian cysts and related torsions are the most common adnexial pathologies in childhood. Diagnostic laparoscopy is the gold standard approach for differential diagnosis. It is aimed to evaluate the data of patients who had surgery for ovarian pathology. STUDY DESIGN: Fifty-three girls of ten years are included the study. Demographic data, medical history, physical examination, laboratory and radiologic investigations, surgical procedure, histopathology, complications and follow up periods are recorded. RESULTS: The median age of children was 13. Excluding the patients who were diagnosed in intrauterine period (n=4), all of the patients had abdominal pain (92%). Laparoscopic cystectomy (56.7%), detorsion and cystectomy (16.9%) and oopherectomy (16.9%) were performed in patients with cysts. Diagnostic laparoscopy (3,8%) and laparoscopic detorsion (5.7%) were performed in patients without cyst. Dermoid cysts were found in three children and teratomas in two. Patients were discharged in postoperative second day. CONCLUSION: Diagnostic laparoscopy is the gold standard approach for differential diagnosis. Laparoscopic approach should be chosen because of shorter hospital stay, shorter healing period, and better cosmetic results. Besides, less pelvic adhesions compared to laparotomy in laparoscopy is important for further fertility.